A synthesis‐analysis of winter oilseed rape yield response to planting density under intensive cropping system in Yangtze River Basin. (9th February 2023) - Cong, Rihuan; Zhong, Zijing; Zhang, Zhi; Liu, Yu; Lu, Zhifeng; Ren, Tao; Li, Xiaokun; Lu, Jianwei
Abstract: Optimal yield is dependent on the collocations between plant population and individual growth. High plant population for direct‐sown winter oilseed rape would be a common method to achieve high yield under intensive cropping systems. We investigated the oilseed rape ( Brassica napus L.) yield response to planting density while considering the productivity environment, nitrogen (N) fertilizer, and sowing date. A synthesis‐analysis was conducted by collecting the density–yield data in the field experiments of oilseed rape from 2000 to 2019 in China. The population yield response to different planting density levels could be described by a quadratic model, with a threshold value of 45–60 plants m −2 . High planting density had no remarkable influence on the attainable population yield due to the decreasing individual potential yield. The population yield increment capacity by the increasing planting density was higher in medium yield environment (i.e., average yield at 1500–2500 kg ha −1 ). The planting density presented a remarkable effect on population yield after the N limitation was relieved. Increasing planting density at 10 4 plants per hectare was equivalent to applying 1.17 kg N fertilizer on population yield, ranging from 0.42 to 4.76 kg under different yield environment levels. Yield loss caused by unsuitable sowing date (especially for the late sowing) could be compensated by increasing planting density. Planting density played a crucial role in adapting other management practices. Optimizing the allocation of plant population and individual growth, and establishing target plant phenotype under high planting density would help achieve high population yield. Core Ideas: A quadratic model explained different planting density levels as a function of yield. An increased population yield capacity by the increasing density was higher in the medium yield state. The planting density presented has a remarkable effect on population yield after the N sufficient. Yield loss caused by unsuitable sowing date could be compensated by increasing planting density.